Gaya Bahasa dan Komunikasi dalam Podcast RINTIK SEDU Episode “Dari Sana : Jodoh Emang Gak Kemana, Tapi di Mana?” - Hasna Putri Aqilah El Mukayyis (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study analyzes the use of language and communication styles in the Rintik Sedu podcast, especially in the episode “form there: Jodoh Emang Gak Kemana, Tapi di Mana”, In the digital era, podcast have become one of the most effective information media. Qualitative research methods are used to describe the diverse language styles and communication styles that are emotional and supportive. The results of the analysis show that the language style used tends to be simple and moderate, while the communication style used is expressive, supportive, and emotional. Thus, the language and communication styles in this podcast succeeded in creating a close relationship with the listeners.